Effective document management : unlocking corporate knowledge - Wiggins, Bob.; Wiggins, Bob. (Aldershot, Hampshire, England ; Brookfield, Vt., USA : Gower, 2000)
This text suggests how document management can be achieved in the context of knowledge management and improvement approaches. The author explains how different technologies can support the life-cycle from creation, indexing, retrieval and communication to disposal or storage. Both strategic and project-level issues are addressed, from developing an information systems strategy, to day-to-day records and document management practice and establishing user requirements for new systems, tendering procedures, system selection and implementation.
Rev. ed. of: Integrated document management. United Kingdom : Elan Business, 1996.
Includes bibliographical references and index.
oif 11/08/15
Loan
Keywords: Business records -- Management -- Data processing; Business records -- Management; Information storage and retrieval systems -- Business